Pelaksanaan Perjanjian Kerja Ditinjau Dari Undang-UndangNomor 13 Tahun 2003 Pada PT Kandang Karya PerkasaDi Kabupaten Sukoharjo - Mahardhika, Gilang, Darsono, S.H., M.H (2016)
Purpose of the research is to know process of a working employment agreement that is not containing rights and duties in detail of employer and employee and legal protection for employee against employer if the agreement is conducted verbally in PT. Kandang Karya Perkasa of Sukoharjo Regency. The research used juridical-normative one with primary data was collected from interview and secondary data was collected from literature. The data was analyzed qualitatively. Results of the research indicated that implementation of verbal employment agreement between employer and employee was in accordance with Act No. 13 of 2003 on Labor Affair of Article 63 paragraph (2) stating that assignment letter as intended in paragraph (1) shall at least contain information about: a. name and address of employee/labor; b. date of starting the job; c. type of work, and d. salary or wage. After the provision has been met, the employer may employ an employee and satisfy rights and duties and legal protection is prevailed.